Aplicación de la Metodología del Aula Virtual para mejorar el crecimiento productivo de los Trabajadores de la Municipalidad Distrital de Elías Soplín Vargas - Rioja - Cavero Ríos, Juan Daniel (2015)
This paper entitled "Application of the methodology of the virtual classroom to enhance productivity growth of workers in the District Municipality of Elias Soplin Vargas Rioja", studies the problem of poor productivity growth of workers in the District Municipality of Elias Vargas Soplin caused by a low awareness of services provided by the municipality and procedures to perform them properly. The methodology of the virtual classroom also known as E-Learning (set of strategies and educational materials accessible via Internet) was used in research as a strategic tool for improving worker productivity. The population used were workers from different areas of the municipality; some of these workers was sampled, the productivity of workers before it was measured and after implementing the methodology of the virtual classroom which was used as a variable stimulus to improve worker productivity, with positive results to achieve a significant improvement